2017
DOI: 10.3389/fpsyg.2017.00322
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the Meaning: Top–Down Effects on Letter Identification

Abstract: Most models of reading agree that visual word recognition is underpinned by a highly interactive network in which both bottom–up and top–down processes contribute. What remains unknown is whether evidence of top–down effects upon letter processing are restricted to word-form level information, or whether meaning-level information also plays a role. Here we sought to investigate top–down semantic influences upon letter detection using semantic manipulations of real word imageability and semantic priming, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Most work has been done with respect to orthographic processing within the left occipitotemporal cortex and fusiform gyrus. Here, a modulation through phonological (Perea et al, 2016) and semantic properties (Whaley et al, 2016;Evans et al, 2017) was found that facilitates performance and neuronal responsiveness (Strijkers et al, 2015). In addition, intrinsic connection between sublexical (sub-word processing within SPL) and orthographic representation (whole-word processing within fusiform gyrus) were found to be modulated by task-intention (Deng et al, 2012), that is not reflected in current models of language decoding (like CDP+; see Figure 1).…”
Section: Introductionmentioning
confidence: 83%
“…Most work has been done with respect to orthographic processing within the left occipitotemporal cortex and fusiform gyrus. Here, a modulation through phonological (Perea et al, 2016) and semantic properties (Whaley et al, 2016;Evans et al, 2017) was found that facilitates performance and neuronal responsiveness (Strijkers et al, 2015). In addition, intrinsic connection between sublexical (sub-word processing within SPL) and orthographic representation (whole-word processing within fusiform gyrus) were found to be modulated by task-intention (Deng et al, 2012), that is not reflected in current models of language decoding (like CDP+; see Figure 1).…”
Section: Introductionmentioning
confidence: 83%
“…decision latencies. Lexical decision is the most frequently used task in the visual word recognition literature to examine semantic effects (Balota & Chumbley, 1984;Cortese & Schock, 2013;Evans et al, 2017). The results of our regression model showed that conceptual familiarity significantly contributed to lexical decision latencies, over and beyond the contribution of other psycholinguistic and semantic variables that have previously shown a facilitatory effect on lexical decision latencies.…”
Section: Discussionmentioning
confidence: 62%
“…It is widely accepted that word-form (e.g., word length), lexical (e.g., objective word frequency) and semantic variables (e.g., imageability, age of acquisition or AoA) influence language processing of written stimuli, as observed using both lexical decision and word naming tasks (Alario & Ferrand, 1999;Baluch & Besner, 2001;Cortese & Schock, 2013;Evans, Lambon Ralph, & Woollams, 2017;Ferrand et al, 2008;Strain & Herdman, 1999;Strain, Patterson, & Seidenberg, 1995;Zevin & Balota, 2000). Some of these variables are mostly based on objective measures (i.e., the number of letters or syllables, the first letter or phoneme of a stimulus, objective word frequencies based on film subtitles All the co-authors contributed equally on this work.…”
mentioning
confidence: 99%
“…More recently, research has come to focus on understanding the visual system and how it represents and processes letters as visual objects, without losing interest, however, in attempting to make written text more comprehensible or helping learners to acquire reading skills more easily (Boles & Clifford, 1989;Fiset et al, 2009;Liu & Arditi, 2001;Mueller & Weidemann, 2012). Collectively, these studies have played a fundamental role in enabling the design and implementation of many well-controlled empirical studies seeking to pin down the dynamics of letter processing (e.g., Evans, Lambon Ralph, & Woollams, 2017;Grainger, Dufau, Montant, Ziegler, & Fagot, 2012;Kinoshita & Kaplan, 2008;Schelonka, Graulty, Canseco-Gonzalez, & Pitts, 2017).…”
mentioning
confidence: 99%